Animation of Film - Mazanec, Martin (Iluminace, 2009)
The text reflects on the nature of the definition of animation and animated film along the lines of Kubelka's discourse, which either considers animation as a supreme film technology, i.e. creating the impression of movement between a series of static photograms, or, for the same reason, condemns it as an empty concept; since cinematography operates on the principle of interesting a series of photograms, the term animation is redundant. The author extends the discursive field of animation to include intermedial intersections and specific contexts of use, conceiving it as a shifting sign that acquires meaning only in the context of a specific message, thus simultaneously cultivating and blurring the term, and thus demonstrating the great theoretical and practical-methodological potential that the medium/technology of animation offers.
Keywords: film theory; film terminology; animated film; animation in film